On-demand generation of nondiffracting Helmholtz–Gauss laser beams - Ly Ly Nguyen Thi; Kuo-Chih Chang; Shu-Chun Chu (Scientific Reports)
Abstract Nondiffracting beams have gained significant interest because of their ability to propagate over long distances without divergence, making them highly valuable in various laser applications. Historically, laser sources for nondiffracting beams were constrained by their symmetry in the cavity’s coordinate system and intracavity elements, which restricted the types of beams that could be directly generated from the cavity. This study presents the first direct generation of nondiffracting Parabolic-Gauss beams, as well as other Helmholtz–Gauss beams with helical wavefronts, directly from a laser cavity. The key technique involves controlling the two end-phase boundaries of a dual-modulation digital laser resonator with a concentric configuration, thereby ensuring stable round-trip conditions for generating various nondiffracting beams. The experimental results demonstrated that the dual-phase modulation digital laser could generate Parabolic-Gauss, Bessel–Gauss, Mathieu–Gauss beams, and even vortex nondiffracting beams. This laser source enables dynamic, real-time adjustment of beam properties, which is highly beneficial for applications requiring nondiffracting beams.